Effect of Experimental Methods on Early Children's Creativity - Addini, Saifuna Nur; Widyasari, Choiriyah (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2021)
The experimental method is one of the learning methods that can help encourage individual abilities by observing objects around them and creating a high sense of curiosity in individuals. With individual experimental methods will add knowledge, gain experience and be able to develop creative abilities. This article aims to review literature reviews, and articles from research related to experimental methods and early childhood creative abilities. Sample: The sample used in this study is a research journal with the topic of experimental methods or creativity according to the criteria of the selected journal, namely: 1) experimental methods, 2) children's creativity, 3) early childhood respondents. Method: The method used in this research is the search for scientific articles from several databases totaling 20 journals consisting of 15 national journals in the last 5 years and 5 international journals over the last 7 years and using certain keywords. The results of the discussion: literature review shows that the experimental method can provide a process for something happening and a solution, which can produce abilities in children, such as children's creativity abilities that can be stimulated by activities using experimental methods. Experimental methods can be provided through the introduction of science, science skills, or science learning. Science activities for early childhood include identifying colors, mixing colors, recognizing plants, recognizing animals, causes of natural events, and so on. This activity is related to the experimental method which also affects the creativity of early childhood. Conclusion: the experimental method is one of the experimental methods that is able to make children find and solve their own problems, this is able to foster creativity in early childhood.